Tobin's q and the Structure-Performance Relationship: Comment - Shepherd, William G. (American Economic Review, 1986)
The exchange of comments between William Shepherd and Michael Smirlock, Thomas Gilligan, and William Marshall (this Review, December 1986) raised two key points that remain unresolved. The first point is whether Tobin's q ratio, a firm's financial market value divided by replacement cost of its assets, is a better measure of firm performance than accounting rates of return. The second point of contention is whether superior performance, however measured, can be attributed to efficiency rather than market power. This paper offers further clarification on both of these points. In Section I the performance measure choice is shown to be influenced by fundamental differences between finance and economics. In Section II, the structure-performance model employed by Smirlock, Gilligan, and Marshall (hereafter, SGM) and Shepherd is shown to be a special case of a more general model allowing for a dependence of the market-share-performance relationship on the concentration ratio. The same data from the original study by SGM (1984) are used in Section III to provide a comparison of SGM's findings with empirical results from an alternative specification of the structure-performance model. This comparison suggests that attributing superior firm performance exclusively to efficiency is not well founded. Concluding remarks are found in Section IV.